Case report: Combination technique of balloon dilation, membrane excision, and topical mitomycin C for the treatment of nasopharyngeal stenosis in a cat - Kwak, Ho Hyun; Kim, Sung Min; Yu, Lina; Kim, Jun Hyung; Woo, Heung Myong (Frontiers in Veterinary Science, 2024)
A two-year-old neutered male Turkish Angora cat presented with respiratory signs, including chronic snoring sounds and dyspnea with open-mouth breathing. Nasopharyngeal stenosis (NPS) was diagnosed based on endoscopy and computed tomography (CT). An attempt was made to break down the membrane, causing stenosis in the nasopharynx through balloon dilation using a valvuloplasty balloon dilation catheter (12 mm × 3 cm) and retroflexed endoscope. The balloon size was selected according to the identified diameter of the stenotic site on nasopharyngeal CT images. The balloon was inflated with radiographic contrast medium and maintained for 2 min; the similar procedure was repeated four additional times. The stenotic membrane was excised after balloon dilation. Topical Mitomycin C (MMC) was then administered to the stenotic region. After 2 weeks, an additional MMC application was repeated to prevent recurrence. The cat remained free of clinical signs without recurrence for 12 months after the most recent procedure. In this study, effective treatment results were obtained using a combination of balloon dilation, membrane excision, and topical MMC for membranous nasopharyngeal stenosis in a cat.